Characterization of TGF-β expression and signaling profile in the adipose tissue of rats fed with high-fat and energy-restricted diets - Sousa-Pinto, Bernardo (2017)
Transforming growth factor beta (TGF-β) plays an important role in the pathogenesis of obesity, influencing the release of inflammation mediators and promoting remodeling and collagen deposition in the adipose tissue (AT). In this context, this work aims to elucidate whether TGF-β and Smad-dependent or Smad-independent signaling pathways contribute to regional differentiation of AT in high-fat diet (HFD) and energy-restricted (ER) rat models. For this, TGF-β, TGF-β receptors I and II, PAI-1 and GLUT4 mRNA levels were quantified by real-time PCR, and western blotting assays allowed the semiquantification of TGF-β and proteins from Smad3, ERK1/2 and Akt signaling pathways in subcutaneous and visceral (epididymal, retroperitoneal and mesenteric) fat depots from control, HFD and ER-treated rats. HFD was associated to increased levels of TGF-β and PAI-1 mRNA in epididymal and retroperitoneal visceral fat depots, while ER diet induced a reduction of TGF-β mRNA levels in mesenteric, but surprisingly an increase in retroperitoneal fat. Regarding the different signaling pathways, contrarily to what was found for Smad3, activation of ERK1/2 and Akt in response to HFD was detected in all the visceral but not in subcutaneous fat depots. ER-treated rats presented a more heterogeneous signaling response, as well as decreased TGF-β receptors expression, in the different visceral fat depots. In conclusion, subcutaneous and visceral AT respond differently to distinct diet patterns regarding TGF-β expression and activated signaling pathways. Furthermore, the present study points that visceral AT should not be understood as a homogeneous entity since that response also varied in the different fat depots.